Theodora goes wild = Theodora wird wild - Buchman, Sidney 1902-1975; MacCarthy, Mary 1882-1953 (Sony Pictures Home Entertainment, 2013)
"The town of Lynnfield is up in arms over the local newspaper running excerpts of a scandalous new novel by Caroline Adams, The Sinner. What they do not know is that Caroline Adams is indeed a local girl"--Warner Archive Collection website
Originally produced in the United States as a motion picture in 1936
Full screen (1.33:1)
Keywords: Screwball comedy; Komödie; Liebesfilm; Spielfilm; Man-woman relationships / Drama; Novelists / Drama; Man-woman relationships; Novelists; screwball comedy; Comedy films; Drama; Feature films; Fiction films; Screwball comedy films; Comédies loufoques (Films); Films comiques; Films de fiction; Film; DVD-Video